2018
DOI: 10.14507/epaa.26.3814
|View full text |Cite
|
Sign up to set email alerts
|

A critique of grading: Policies, practices, and technical matters

Abstract: In recent years there was been a raft of criticisms of the way that grades (or marks) are assigned to students. The purpose of this paper is to examine the strengths and weaknesses of grading systems and grading practices, drawing upon both historical and contemporary research and writing. Five questions are used to frame the review and organize the paper. They are: (1) Why do we grade students? (2) What do grades mean? (3) How reliable are students’ grades? (4) How valid are students’ grades? and (5) What are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 25 publications
(32 reference statements)
0
28
0
Order By: Relevance
“…Further, the studied case can serve as an example of the need to consider side effects in educational research (Zhao, 2017). This may be particularly important for issues like grading, which on the one hand is an accepted (Schneider & Hutt, 2014) and institutionalized (Salomonsen & Andersen, 2014) aspect of schooling, but on the other hand is an activity that is constantly criticized for shortcomings in practical execution (Anderson, 2018;Brookhart, 2013Brookhart, , 2015. As intended, criterion-referenced grading in Swedish compulsory school has turned into a results measure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the studied case can serve as an example of the need to consider side effects in educational research (Zhao, 2017). This may be particularly important for issues like grading, which on the one hand is an accepted (Schneider & Hutt, 2014) and institutionalized (Salomonsen & Andersen, 2014) aspect of schooling, but on the other hand is an activity that is constantly criticized for shortcomings in practical execution (Anderson, 2018;Brookhart, 2013Brookhart, , 2015. As intended, criterion-referenced grading in Swedish compulsory school has turned into a results measure.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from providing insights into the Swedish case, 2 the findings can give input to research about grading policies and to policy discussions in other educational contexts (cf. Anderson, 2018). Not only does grading have an impact on teaching and what is done in school, it also influences who pupils become in terms of achievement (Ball, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Battistone, Buckmiller, and Peters (2019) found that teacher education training on progressive assessment practices was inconsistent at best. Further, as Anderson (2018) asserts, typical classroom assessment courses in teacher preparation programs typically devote only a single chapter at most to grading practices. Therefore, high school leaders will need to provide ongoing support for new teachers through in-service workshops and professional development to further refine their knowledge and skill level regarding methods and rationales for SBG.…”
Section: Discussionmentioning
confidence: 99%
“…Another way to address the percent scale issues is to use the concept of standards-based grading (discussed in the review by Brookhart et al [31] and references therein). This method asks students to demonstrate proficiency in certain areas, with the instructor providing ordinal grades such as well below proficiency, approaching proficiency, proficient, and excellent, that describe the path to proficiency [32]. This approach has been used [12] in college physics classes but, because the method requires students to be able to have multiple opportunities to attempt the same proficiency, it is difficult to accomplish with the large class sizes that are typical of introductory science courses.…”
Section: Alternative Grade Scales and Practicesmentioning
confidence: 99%
“…This means that a grade of "zero" is less disastrous for students. This scale is mathematically similar to the practice of minimum grading, and instructors using standards-based grading also sometimes use the integers on a 4.0 scale to mean different levels of proficiency [12,32], so aspects of this scale exist in both of the other alternatives we describe. Because the 4.0 scale mitigates many of the criticisms of the percent scale, many suggest it as an alternative to percent scale grading.…”
Section: Alternative Grade Scales and Practicesmentioning
confidence: 99%